Understanding the microbiome of diabetic foot osteomyelitis: insights from molecular and microscopic approaches. (March 2019) - Johani, K.; Fritz, B.G.; Bjarnsholt, T.; Lipsky, B.A.; Jensen, S.O.; Yang, M.; Dean, A.; Hu, H.; Vickery, K.; Malone, M.
Abstract: Objectives: Rigorous visual evidence on whether or not biofilms are involved in diabetic foot osteomyelitis (DFO) is lacking. We employed a suite of molecular and microscopic approaches to investigate the microbiome, and phenotypic state of microorganisms involved in DFO. Methods: In 20 consecutive subjects with suspected DFO, we collected intraoperative bone specimens. To explore the microbial diversity present in infected bone we performed next generation DNA sequencing. We used scanning electron microscopy (SEM) and peptide nucleic acid fluorescent in situ hybridization (PNA-FISH) with confocal microscopy to visualize and confirm the presence of biofilms. Results: In 19 of 20 (95%) studied patients presenting with DFO, it was associated with an infected diabetic foot ulcer. By DNA sequencing of infected bone, Corynebacterium sp. was the most commonly identified microorganism, followed by Finegoldia sp., Staphylococcus sp., Streptococcus sp., Porphyromonas sp., and Anaerococcus sp. Six of 20 bone samples (30%) contained only one or two pathogens, while the remaining 14 (70%) had polymicrobial communities. Using a combination of SEM and PNA-FISH, we identified microbial aggregates in biofilms in 16 (80%) bone specimens and found that they were typically coccoid or rod-shaped aggregates. Conclusions: The presence of biofilms in DFO may explain why non-surgical treatment of DFO, relying on systemic antibiotic therapy, may not resolve some chronic infections caused by biofilm-producing strains.